THE EFFECTOF MIND MAPPING TO IMPROVETHE ABILITY TO DOTHE OPERATION OF SUMMING DOWNWARD ROWSOF DYSCALCULIASTUDENTS - Ade Setiawati; Damri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the effect of mind mapping to increase the ability of the operation of summing downward rows of dyscalculia students. This research utilized Single Subject Reseacrh (SSR) with A-B-A design. A-B-A design consisted of three conditions, namely the initial baseline (A1), intervention (B), and the final baseline (A2). This research data were obtained from a male dyscalculia student at grade III elementary school through fourteen observations by implementing mind mapping. Then, the data were analyzed by using visual analysis of graphic data. The ability to do the operation of summing downward rows for students in the initial baseline observation (A1) obtained a percentage of 0%, 0%, 0% in three times observations. Then, the intervention (B) was carried out by applying mind mapping and it was found that the percentage increased for 90%, 100%, 100%, 100%, 100% in five times observations. Finally, the observation at the final baseline (A2) found that the percentage increased by 35%, 70%, 80%, 100%, 100%, 100% in six times observations. Based on the results of the analysis, it was found that applying mind mapping was effective in increasing the ability to perform the operation of summing downward rows of dyscalculia students.